ORGANIZATIONAL SUPPORT FOR BUSINESS DEVELOPMENT AT THE REGIONAL LEVEL - Lesnaya , Olena (Theory and Practice of Public Administration, 2020)
The article reviewed organizations which activities aim to develop business activity at Kharkiv region level. Department of Economics and External relations of Kharkiv Regional State Administration, Department of competitive growth of the region of Kharkiv Regional State Administration, Kharkiv Regional Business Development Fund, Regional Council, “Private Employers Association” Kharkiv regional public organization, Kharkiv Chamber of Commerce and Industry, Employers’ Union of Kharkiv Region, Regional Representative Office of International Chamber of Commerce “ICC Ukraine” in Kharkiv Region, Union of Industrialists and Entrepreneurs of Kharkiv Region – Regional Office of All-Ukrainian public organization “Ukrainian Union of Industrialists and Entrepreneurs”. The purpose of the assignment and main functions on business development promotion of the above mentioned organizations at Kharkiv region level have been defined. There has been formed a powerful organization of business support and creation of favorable conditions of conducting business. You can obtain the information about the organizations mainly through the Internet but businessmen do not always have possibilities and enough time to find needed information. Therefore we consider this advisable to increase the volume of social advertising of activities of business support organizations through the press or local TV. It can be a series of programs, clips in the news or social advertising. It is hoped that the above measures will expand the level of awareness of the citizens of the additional opportunities for business development at regional level and will promote the growth.